Duodenal eosinophilia and the link to anxiety: A population‐based endoscopic study. Issue 10 (9th March 2021) - Ronkainen, Jukka; Aro, Pertti; Jones, Mike; Walker, Marjorie M.; Agréus, Lars; Andreasson, Anna; Talley, Nicholas J.
Abstract: Introduction: The concept of gut‐to‐brain communication via microbial or inflammatory pathways is gaining increased attention but genuine pathology directly linking gut perturbation to anxiety is lacking. We hypothesized that duodenal eosinophilia, as known to occur in functional dyspepsia (FD), may be an underlying cause of anxiety and may help explain the striking association between FD and anxiety. Methods: Randomly selected subjects from the national population register of Sweden completed the validated Abdominal Symptom Questionnaire; 1000 completed esophagogastroduodenoscopy and the Hospital Anxiety and Depression Scale questionnaire. Duodenal biopsies were obtained from 1 st (D1) and 2 nd portion (D2). Eligible subjects who underwent endoscopy ( n  = 887) were invited to participate in a 10‐year follow‐up study with the same questionnaires. Among endoscopy normal subjects, FD was identified by Rome criteria, and controls were symptom free. Duodenal eosinophilia was based on pre‐defined cut‐offs. Finding are reported as odds ratios (ORs) with 95% confidence interval and p‐value. Results: The study population comprised 89 cases with FD and 124 healthy controls (mean age 62 years, SD 12, 34% male). Clinical anxiety at follow‐up was elevated in those with D1 eosinophilia at baseline considering either new‐onset anxiety (OR = 4.5, 95% CI 0.8, 23.8; p  = 0.08) or follow‐up anxiety adjusting for baseline anxiety (OR = 4.51 (95% CI 1.03, 19.81; p  = 0.046). Conclusion: Duodenal eosinophilia may potentially be a mechanism linked to anxiety independent of FD. Abstract :